2022
DOI: 10.3389/fphar.2022.968226
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of quercetin on kidney diseases: From chemistry to herbal medicines

Abstract: Kidney injuries may trigger renal fibrosis and lead to chronic kidney disease (CKD), but effective therapeutic strategies are still limited. Quercetin is a natural flavonoid widely distributed in herbal medicines. A large number of studies have demonstrated that quercetin may protect kidneys by alleviating renal toxicity, apoptosis, fibrosis and inflammation in a variety of kidney diseases. Therefore, quercetin could be one of the promising drugs in the treatment of renal disorders. In the present study, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 93 publications
1
10
0
Order By: Relevance
“…63,64 Meanwhile a large body of evidence demonstrated the renoprotective effects of quercetin through anti-inflammatory activity and attenuation of apoptosis and fibrosis. [65][66][67] The histopathological finding of the current study greatly supports the biochemical test; where a pronounced improvement has been observed in the combination therapy via clear improvement in the lesion scoring, tissue degeneration, and necrosis.…”
Section: Discussionsupporting
confidence: 78%
“…63,64 Meanwhile a large body of evidence demonstrated the renoprotective effects of quercetin through anti-inflammatory activity and attenuation of apoptosis and fibrosis. [65][66][67] The histopathological finding of the current study greatly supports the biochemical test; where a pronounced improvement has been observed in the combination therapy via clear improvement in the lesion scoring, tissue degeneration, and necrosis.…”
Section: Discussionsupporting
confidence: 78%
“…The nephroprotective effects of quercetin have been reported (70 71). The nephroprotective effects of quercetin have been linked to its ability to inhibit the formation of malondialdehyde, scavenge reactive oxygen species, and activate the expression of nuclear factor erythroid 2-related factor 2 and renal heme oxygenase 1, which are important in boosting the production of antioxidant moieties (72).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, a Sirtuin-1 and Sirtuin-3 activator, can be widely obtained from many fruits and vegetables, and exhibits wide biological effects in resisting inflammation, diabetic and microbial activities ( Chen et al, 2021 ; Zymone et al, 2022 ). Quercetin also shows renoprotective effects against nephrotoxicity, AKI and CKD ( Lu et al, 2021 ; Chen et al, 2022 ). It has been found quercetin can upregulate PINK1 and Parkin expression via Sirtuin-1 activation.…”
Section: Natural Products For Regulating Mitochondrial Functionmentioning
confidence: 99%